PLA Degradation and PLA-Degrading Bacteria: A Mini-Review Journal: Key Engineering Materials - Joyce Cynthia, Jalani; Zatul Iffah, Mohd Arshad (Trans Tech Publications, Switzerland, 2022)
Polylactic acid (PLA) is not new to the world of science, since the application of PLA can be found in various industries such as biomedical, agricultural, and packaging. Despite the amazing properties shown by PLA, it still has a setback in terms of waste disposal of PLA. Since PLA is more resistant towards bacterial attack, it prolonged the decomposition of PLA disposed in the environment. Therefore, PLA microbial degradation and enzymatic degradation needs to be highlighted since most PLA waste will end up in the landfill. Most PLA-degrading can be found in the genus family Amycolatopsis, and a few can be found in the genus Lentzea, Kibdelosporangium, Paecilomyces, Thermomonospora, and Thermopolyspora. The enzymatic degradation of PLA is mostly studied relating to enzyme proteinase K, serine protease, and even hydrolase. This review paper aims to discuss the microbial degradation mechanism of PLA as well as the types of microorganisms and enzymes that involve in the biodegradation of PLA.